Unraveling the blood transcriptome after real-life exposure of Wistar-rats to PM2.5, PM1 and water-soluble metals in the ambient air. (2020) - Frydas, Ilias S.; Kermenidou, Marianthi; Tsave, Olga; Salifoglou, Athanasios; Sarigiannis, Dimosthenis A.
Graphical abstract: Highlights: Development of a "real-life" exposure system to ambient PM1 and PM2.5 particles for Wistar rats. Blood transcriptome analysis identified differentially expressed genes as candidate biomarkers in PM1 and PM2.5 groups. Pathway analysis revealed differentially regulated gene expression in inflammation signaling. Identification of candidate metals for possible correlation with the identified candidate genes leading to the development of AOPs. Abstract: Exposure to particulate matter (PM) is one of the most important environmental issues in Europe with major health impact. Various sizes of PM are suspended in the atmosphere and contributes to ambient air pollution. The current study aimed to explore the differential gene expression in blood, and the effect on the respective biological signaling pathways in Wistar rats, after exposure to PM2.5 and PM1 ambient air particles for an eight-week period. A control group was included with animals breathing non-filtered atmospheric air. In parallel, filtered PM2.5 and PM1 was collected in separate samplers. The results after whole genome microarray analysis showed 23 differentially expressed genes (DEGs) between control and PM2.5 group. In addition, pairwise comparison between control and PM1 group displayed 5635 DEGs linked to 69 biological pathways involved in inflammatory response, cell cycle and carcinogenicity. The smaller the size of the inhaled particles, the more gene alterations are triggered compared to non-filtered air group. More specifically, in inflammation signaling procedures differentially regulated gene expression was shown for interleukin-4 (IL-4), IL-7, IL-1, IL-5, IL-9, IL-6 and IL-2. We have identified that RASGFR1, TRIM65, TRIM33, PLEKHB1, CAR4, S100A8, S100A9, ALPL, NP4 and the PROK2 genes are potential targets for the development of adverse outcome pathways (AOPs) due to "real-life" exposure of Wistar rats. Particle measurements during the exposure period showed elevated concentrations of Fe, Mn and Zn in both PM1 and PM2.5 filter fractions, and of Cu in PM2.5. In addition, water-soluble concentration of metals showed significant differences between PM1 and PM2.5 fractions for V, Zn, As, Pb and Mn. In summary, in this study specific gene biomarkers of exposure to ambient air have been identified and heavy metals that are possibly linked to their altered regulation have been found. The results of this research will pave the way for the development of novel AOPs concerning the health effects of the environmental pollution.